Detection of 185 delAG Mutation in Breast Cancer 1 BRCA1 Gene Among Libyan Women Attending Breast Cilinc - Essarbout, Amel A.; Marwan, Mohamed B.Marwan; Aribi, Nuridin H. (جامعة طرابلس - كلية التربية, 2012)
Breast cancer is associated with mutation in the 185delAG nucleotide of the coding exon on the BRCA1 gene. A simple and rapid method for the detection of 185delAG mutation in BRCA1 gene using mutagenically separated polymerase chain reaction (MSPCR) assay and agarose gel electrophoresis analysis. Thirty Libyan females (26 diagnosed with breast cancer and 4 normal as control) were genetically screened by this method for 185delAG mutation. Appearance of two bands in the electrophoresis analysis is an indication for the mutation in the BRCA1 gene and could be high risk for the development of breast cancer. Results of the study showed also that 185delAG mutation is presented as high as 61.5% of the subjects.
Keywords: ليبيا -- سرطان الثدي -- الجراحة العامة -- الطفرات الجينية